Homoeopathic Management Of Irritant ContactDermatitis – Case Report - C., Veerabhadrappa; Desai, Kirtida; Desai, Poorav; A. Moolabharati, Jyoti; Reddy.K.H., Santosh (International Journal of Psychosocial Rehabilitation, 2020)
Skin, being the most exterior part of the body, is one of the important sense organs and comes with it a great deal of aesthetic/cosmetic problems. Asian-type skin is more prone to present with postinflammatory hyperpigmentation, melasma, lentigines, and freckles. The main skin diseases reported are acne, atopic dermatitis, and viral infections.Among the hypersensitivity diseases, dermatitis as a subgroup stands first with a rate of 24.50% of the total. Among the dermatitis group, contact dermatitis (17.54% of the total) is the most commonly reported skin disease.